Influential Article Review - The Market and Corporate Social Responsibility: Towards a Combined visionary Agenda - Tierney, Haydon; Quintana, Taylor; Butler, Todd (Journal of Leadership, Accountability and Ethics, 2019)
This paper examines corporate social responsibility. We present insights from a highly influential paper. Here are the highlights from this paper: The aim of this study is to develop a comprehensive framework and propositions showing the integration of market orientation (MO) as an economic-oriented strategy and corporate social responsibility (CSR), as a socially–oriented strategy for business performance (BP). A review of literature on the three constructs of MO, CSR and BP facilitated the development of the framework and a number of research propositions. An integrated conceptual framework of economic and social strategies is constructed based on prior conceptualisation of MO and CSR. In total, twenty-six (26) propositions are developed based on the integrated conceptual framework. An empirical examination of the model will clarify further, relations among the variables and then authenticate the developed model and propositions. The study provides practitioners with a framework and the accompanying propositions for decision making with respect to their strategic choices and performance. The conceptual framework and the proposition developed when implemented are expected to enhance both the firm and customer value which has a wider implication for the society. The novelty in this research is the common antecedents of both MO and CSR. This research augments the few studies on the integration of MO and CSR. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.